Impact of regional-scale atmospheric circulation patterns on winter air temperature variability in the Svalbard area - Bednorz, Ewa; Tomczyk, Arkadiusz M.; Czernecki, Bartosz; Piękny, Miłosz (Polish Polar Research, 2024)
Significant increasing trends in the air temperature were found both in the surface station of Svalbard Lufthavn and in the low-tropospheric temperature field over the Atlantic Arctic. The variability in temperature, as well as the multiannual trend, is at least three times bigger in the winter months than in summer. An attempt was made to explain the high day-to-day variability in the winter air temperature by the daily variability in the regional pressure field and circulation conditions. Six regional-scale circulation patterns were found by applying the principal component analysis to the mean daily sea level pressure (SLP) reanalysis data and their impact on the low-tropospheric air temperature variability was determined. A bipolar pattern, with a positive center over Greenland and a negative center over the White Sea, dominates in the region and strongly influences the air temperature field at 850 hPa geopotential height (correlation coefficients up to –0.65). The second pattern that impacts the temperature field in the Atlantic Arctic is the one with a center of action over Svalbard (mostly a low-pressure center in winter), strongly influencing the air temperature over the Barents Sea. The remaining circulation types, explaining only 5–8% of the total variance of the SLP field each, do not modify significantly the air temperature at 850 hPa geopotential level over the Atlantic Arctic, and none of the circulation types seems to influence the multiannual temperature trends.